Юлька: [повесть] / Майя Московкина - Московкина Майя Викторовна (Удмуртия, 2017)
Экземпляры: (20201014) / Инвентарный номер: 41567 / Цена: 1800.00 / Сис.шифр: 84(2=664.1) / Авт.знак: М 82 / ГРНТИ: 17.82 / ББК: 84(2=664.1)